INNOVATING ENGLISH AS A FOREIGN LANGUAGE (EFL) INSTRUCTION: A MODERN APPROACH (Konferensiyalar | Conferences, 2024)
This article explores innovative approaches to English as a Foreign Language (EFL) instruction, focusing on technology integration, project-based learning, the flipped classroom model, and Content and Language Integrated Learning (CLIL). By reviewing literature and discussing methods and results, it highlights the effectiveness of these methodologies in enhancing language learning outcomes, fostering critical thinking, communication skills, and cultural competence among learners.